Acceptance of beef obtained through genetic modification and cloning in university students and working adults in southern Chile - Schnettler, Berta; Velásquez, Carlos; Lobos, Germán; Orellana, Ligia; Sepúlveda, José; Salinas-Oñate, Natalia; Adasme-Berríos, Cristian; Grunert, Klaus G. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
In order to compare the acceptance of beef obtained from a conventionally bred, cloned or genetically modified (GM) animal by working adults and university students, and to identify consumer segments in both subsamples, a survey of 400 people in southern Chile was applied, distributed by means of proportional allocation. Using a conjoint analysis in the total sample, it was determined that the production technology was more important than the price, origin, presentation or breed of the animal. The consumers preferred Argentinean beef, cut, from a conventional animal, at the lowest price. In both subsamples one segment was sensitive to the production technology, one to the price and one to the origin of the meat. Nevertheless, the proportion of adults who rejected cloning and GM was greater, whereas a significant proportion of students viewed meat from a cloned or GM animal positively. In both subsamples, the groups sensitive to the origin had a positive view of beef from a GM animal. The groups in the subsample of students were differentiated by the frequency of beef consumption. In both subsamples, the segments did not differ in the level of satisfaction with their food-related life.